Obecność . niezależne pismo literackie, no. 20, 1987 - Stolarczyk, Janusz; Śmigielski, Zbigniew; Ratajczak, Maciej; Herbst, Lothar; Hoffmann, Krzysztof; Mulak, Jacek (Inicjatywa Wydawnicza Aspekt, 1987)
Creation and circulation: Winner of the Solidarity Cultural Prize for 1986. Published reviews of independent literature.